2020
DOI: 10.1055/s-0040-1710143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Osteocalcin Levels in Saliva of Periodontitis Patients and Their Correlation with the Disease Severity: A Cross-Sectional Study

Abstract: Objectives The present study aimed to investigate osteocalcin levels in saliva of healthy and periodontitis patients and correlate these levels with periodontitis severity. Materials and Methods This cross-sectional study was conducted in a hospital setup. A total of 95 individuals participated in the study with 46 subjects in group I (healthy individuals) and 49 subjects in group II (mild, moderate, and severe chronic periodontitis patients). A detailed assessment of clinical periodontal parameters and alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…After further exclusion of five studies, only eight studies met the inclusion criteria for this review. [9][10][11][12][13][14][15][16] No studies were found in the bibliographies of the included articles during manual search. The included articles consisted of six case reports, [10][11][12][13][14]16 a retrospective study, 9 and a prospective study.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…After further exclusion of five studies, only eight studies met the inclusion criteria for this review. [9][10][11][12][13][14][15][16] No studies were found in the bibliographies of the included articles during manual search. The included articles consisted of six case reports, [10][11][12][13][14]16 a retrospective study, 9 and a prospective study.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…12 The intracellular and extracellular pathways of saliva secretion in the oral cavity make it a diagnostic medium for many diseases such as oral cancer, periodontal diseases, dental caries, oral lichen planus, and systemic diseases. 13,14 Also, saliva has been proven as a detecting biofluid for viruses such as human immunodeficiency virus, human papillomavirus, hepatitis A, hepatitis C, Ebola, Zika, and the severe acute respiratory syndrome virus family. 15,16 Saliva contains a host of antimicrobial factors including enzymes and antibodies such as salivary immunoglobulin A (sIgA).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms underlying periodontitis are unclear. Bacterial pathogens are associated with the onset and progression of periodontal disease [9,10]. Consideration of some of the more general aspects of microbial dental biofilm, including the development, heterogeneity, microbial succession, composition, structure, and mechanisms of dental biofilm formation, should precede the discussion of the microbial composition of the gingival crevice (subgingival dental biofilm).…”
Section: Sachio Tsuchida and Tomohiro Nakayamamentioning
confidence: 99%
“…3 Several cytokines or proteins, including tumor necrosis factor, interleukin 8 (IL-8), interleukin (IL-1), interleukin (IL-6), interleukin 10 (IL-10), osteocalcin, and many others have been reported to have an association with periodontal disease progression. [4][5][6] These cytokines have also been proposed as potential diagnostic or predictive biomarkers for periodontitis. Among individuals affected with chronic periodontal disease worldwide, a variable degree of different cytokines' production has been observed, and studies have been conducted to reduce their salivary concentration.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several cytokines or proteins, including tumor necrosis factor, interleukin 8 (IL-8), interleukin (IL-1), interleukin (IL-6), interleukin 10 (IL-10), osteocalcin, and many others have been reported to have an association with periodontal disease progression. 4 5 6 …”
Section: Introductionmentioning
confidence: 99%